Life‐history predicts past and present population connectivity in two sympatric sea stars. Issue 11 (23rd April 2017) - Puritz, Jonathan B.; Keever, Carson C.; Addison, Jason A.; Barbosa, Sergio S.; Byrne, Maria; Hart, Michael W.; Grosberg, Richard K.; Toonen, Robert J.
Abstract: Life‐history traits, especially the mode and duration of larval development, are expected to strongly influence the population connectivity and phylogeography of marine species. Comparative analysis of sympatric, closely related species with differing life histories provides the opportunity to specifically investigate these mechanisms of evolution but have been equivocal in this regard. Here, we sample two sympatric sea stars across the same geographic range in temperate waters of Australia. Using a combination of mitochondrial DNA sequences, nuclear DNA sequences, and microsatellite genotypes, we show that the benthic‐developing sea star, Parvulastra exigua, has lower levels of within‐ and among‐population genetic diversity, more inferred genetic clusters, and higher levels of hierarchical and pairwise population structure than Meridiastra calcar, a species with planktonic development. While both species have populations that have diverged since the middle of the second glacial period of the Pleistocene, most P. exigua populations have origins after the last glacial maxima (LGM), whereas most M. calcar populations diverged long before the LGM. Our results indicate that phylogenetic patterns of these two species are consistent with predicted dispersal abilities; the benthic‐developing P. exigua shows a pattern of extirpation during the LGM with subsequent recolonization, whereas the planktonic‐developing M. calcar shows a pattern of persistence and isolation during the LGM with subsequent post‐Pleistocene introgression. Abstract : Using a combination of mitochondrial DNA sequences, nuclear DNA sequences, and microsatellite genotypes, we show that the benthic‐developing sea star, Parvulastra exigua, has lower levels of within‐ and among‐population genetic diversity, more inferred genetic clusters, and higher levels of hierarchical and pairwise population structure than Meridiastra calcar, a species with planktonic development. Our results indicate that phylogenetic patterns of these two species are consistent with predicted dispersal abilities; the benthic‐developing P. exigua shows a pattern of extirpation during the LGM with subsequent recolonization, whereas the planktonic‐developing M. calcar shows a pattern of persistence and isolation during the LGM with subsequent post‐Pleistocene introgression.